Perception of the use of the teacher's virtual whiteboard by students in basic mathematics of a public university, Lima 2022 - Jiménez Castañeda , Alejandro (2024)
Historically, virtual whiteboards emerged with the rise of digital technologies in the late twentieth and early twenty-first centuries, offering an interactive alternative to traditional physical blackboards. The virtual whiteboard, an emerging tool in distance education, is the object of study of the present research, conducted in a public university, to evaluate its use in the teaching of basic mathematics to 36 students, using a quantitative approach, non-experimental design and descriptive sub-design. In the instrumental dimension, teachers showed limitations in the technical handling of the tool. Cognitively, the integration of the virtual whiteboard in teaching strategies was minimal. Behaviorally, students interacted little with the tool, and axiologically, no significant change was perceived in the educational values promoted. These results suggest the need to train teachers in the effective use of virtual whiteboards and to foster an educational culture that values and takes advantage of digital technologies. They also highlight the importance of further research and development of methodologies that integrate these tools more effectively into the educational process.